The distinctive terminology in S̆arḥ al-kāfiya by Raḍī l-Dīn al-'Astarābād̲ī - Sheyhatovitch, Beata (Studies in Semitic languages and linguistics, 2018)
In The distinctive terminology in Šarḥ al-Kāfiya by Raḍī l-Dīn al-ʼAstarābāḏī Beata Sheyhatovitch presents a structured and systematic study of a seminal treatise in the medieval Arabic linguistic tradition. The treatise's author, al-ʼAstarābāḏī (d. circa 1289), is widely considered the most brilliant grammarian of the later classical period. The author's analysis of his terminology reveals the extent of his originality, and of the influence that other Islamic sciences (logic, jurisprudence, theology) had on his writings. The comprehensiveness and the unique approach, which uses texts from various medieval Islamic disciplines to clarify the terminology, make this book an excellent and innovative tool. It provides scholars and ordinary readers with tools for a deeper understanding of al-ʼAstarābāḏī as well as other medieval Arab grammarians.